Swachh Bharat Mission : A Missed Opportunity for the Indian Economy - Kumar, Avnish (Arthshastra Indian Journal of Economics & Research, 2018)
On October 2, 2014, the Government of India launched the Swachh Bharat Mission (SBM) throughout the country as a national movement. The aim of this campaign is to achieve the vision of â€˜Clean Indiaâ€™ by October 2, 2019. This mission, apart from being a cleanliness drive, is certainly going to give a boost to the Indian economy if planned and executed properly. Health, tourism, and rural development are some of the areas expected to be positively impacted by this campaign. The estimated cost of this campaign is ` 1.96 trillion. India could channelize investment under SBM andÂ reap its potential economic benefits. These impacts would bring positive change in GDP and employment in India. This paper mainly analyzed the Central governmentâ€™s contribution in funding SBM. The study found that the development under the mission was not able to meet its expectations. It was observed that there is a lack of effort on part of Central and State governments. Even after 3 years of the SBM campaign, the Central government funding has been inadequate. Not even half of the funds have been allocated. The state governments have not utilized the funds allocated to them. The governmentâ€™s expenditure in information and communication is abysmally low. The study found that the state governments were unable to mobilize funds from corporate businesses under CSR. However, the available statistics on physical progress of SBM certainly appeared promising to achieve its vision.